Pelatihan Pemasaran Produk UMKM Melalui Sarana Media Sosial Di Desa Cimarga, Banten - Lina Aryani; Diana Triwardhani; Pusporini (Jurnal Pengabdian Pada Masyarakat, 2022)
MSME PRODUCT MARKETİNG TRAİNİNG THROUGH SOCİAL MEDİA PLATFORMS İN CİMARGA VİLLAGE, BANTEN. Cimarga village is located in the government area of ​​Lebak Regency, Banten. Partners who become objects are MSME actors, especially the Odeng Honey business, the Lebak Typical Cake business, and the Baduy Craft business. Currently, the development of products made by SMEs in Cimarga Village has not been maximized. This is because the marketing or promotion of their products has not been maximized. The goal to be achieved from this community service activity is to improve the quality of their product marketing by utilizing social media as a means of product promotion. In general, the method of service carried out to partners is in the form of socialization / counseling related to product marketing and the use of IT technology and digital media in marketing products that have been previously developed by partners. Based on the results of comunity service, there is an increase in the understanding of business actors regarding product marketing. For the level of understanding of the definition of product marketing, there is an increase in understanding of 46.7%. Then for understanding the types of marketing mix there is an increase in understanding of 53.3%. Then for the understanding of the use of social media as a means of promotion there was an increase of 46.7%. The team will continue to provide assistance to business actors in Cimarga Village so that their business can continue to grow.